Investigating the impact of lean manufacturing practices on operational performance - Nizam Hafiz, Bandi; Ahmad Nazif, Noor Kamar; Cheng, Jack Kie (Penerbit UMP, 2022)
In order to remain competitive and resilient in business, manufacturing companies must improve their operational performance continuously. Superior performance can no longer be achieved with abundance of time, resources, and money, but the right approaches and tools will allow companies to perform better with greater flexibility. As manufacturing companies try to identify the most beneficial approach, many conclude that Lean Manufacturing (LM) practices are the way to go. LM practices may seem promising at first, but its implementation doesn’t always produce the desired results, and not all LM tools are universally applicable. Choosing the wrong tool might throw off the entire process though initially it meant to improve. Therefore, this study aims to determine the most used of LM tools and how these tools can impact the operational performance. A total of eleven completed responses were collected in the survey through convenience sampling method. Empirical results through descriptive analysis revealed that usage of LM tools such as 5S and Kaizen can lead companies in improving their processes. While lack of knowledge and resistance to change are the major barriers in practicing LM.